Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1152/ajpendo.00283.2007
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein hypoglycemia is essential for full induction of hypoglycemia-associated autonomic failure with slow-onset hypoglycemia

Abstract: Matveyenko AV, Bohland MA, Saberi M, Donovan CM. Portal vein hypoglycemia is essential for full induction of hypoglycemiaassociated autonomic failure with slow-onset hypoglycemia. Am J Physiol Endocrinol Metab 293: E857-E864, 2007. First published July 17, 2007; doi:10.1152/ajpendo.00283.2007.-Antecedent hypoglycemia leads to impaired counterregulation and hypoglycemic unawareness. To ascertain whether antecedent portal vein hypoglycemia impairs portal vein glucose sensing, thereby inducing counterregulatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Of note, altered neural feedback from the hepatoportal region to the brain has been previously shown to alter counterregulatory hormone secretion in the setting of hypoglycemia, albeit under very different experimental conditions. Elegant studies by Donovan and colleagues (24)(25)(26)(27) showed that denervation of the mesenteric region in the rat can alter the counterregulatory responses to insulin-induced hypoglycemia. This effect was only observed, however, when the fall in plasma glucose was slow (i.e., ~0.5 mg/dl/min), whereas disruption of neural input was of no consequence when the fall of the plasma glucose level was rapid (~1.3 mg/dl/min).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, altered neural feedback from the hepatoportal region to the brain has been previously shown to alter counterregulatory hormone secretion in the setting of hypoglycemia, albeit under very different experimental conditions. Elegant studies by Donovan and colleagues (24)(25)(26)(27) showed that denervation of the mesenteric region in the rat can alter the counterregulatory responses to insulin-induced hypoglycemia. This effect was only observed, however, when the fall in plasma glucose was slow (i.e., ~0.5 mg/dl/min), whereas disruption of neural input was of no consequence when the fall of the plasma glucose level was rapid (~1.3 mg/dl/min).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism appears to be critical for the initiation of food intake, rather than the termination of feeding upon its inhibition (104). However, in hypoglycemic conditions the vagal branch does not appear to trigger feeding except in slow-onset hypoglycemia (56). Rapid-onset hypoglycemia is detected by the brain but, not by the liver (19, 86).…”
Section: Hepatic Afferent Nervesmentioning
confidence: 99%
“…Hypoglycemia detection is not mediated by vagal afferents [99,100], but does involve the capsaicin-sensitive primary spinal afferent nerves [101]. It has also been suggested that portal vein glucose sensors only play a key role in the response to slow-onset hypoglycemia [102], but that the primary place of detection shifts to other loci such as the brain when hypoglycemia develops rapidly [103,104].…”
Section: Glucose Sensingmentioning
confidence: 99%